Β-Decay properties of neutron-rich yttrium isotopes. (29th October 2021) - Farooq, Fakeha; Nabi, Jameel-Un; Shehzadi, Ramoona
Abstract: In this study, we have reported key nuclear properties of weak β -decay processes on Yttrium isotopes for the mass number range A = 101 − 108. This mass region has importance while dealing with astrophysical r-process abundances. Our study might be helpful in r-process simulations. We have computed charge-changing strength distributions, β -decay half-lives, β -delayed neutron emission probabilities and β − (EC) weak rates under stellar conditions. We have performed microscopic calculations based on deformed proton-neutron quasi-particle random phase approximation (p–n-QRPA) over a wide temperature (10 7 − 3 × 10 10 ) K and density (10 − 10 11 ) g/cm 3 domain. Unique first-forbidden (U1F) transitions have been included in the calculations in addition to the allowed transitions. A significant decrease in calculated half-lives in ceratin cases, e.g., in 107 Y ( 108 Y) by about 67% (42%), has been observed because of the contribution from U1F transitions. We have compared present results with measured and theoretical works. A good agreement of our half-lives with experimental data is observed.